ASSESSMENT OF ENTREPRENEURIAL MARKETING PERFORMANCE IN SMALL AND MEDIUM FOOD AND NON-FOOD INDUSTRY IN INDONESIA USING IPA ANALYSIS - Gemina, Dwi; Harini, Sri; Sudarijati, Sudarijati (Jurnal Aplikasi Manajemen, 2019)
This study aims to analyze perceptions and expectations on SMIs and establish strategies and policies to develop SMI marketing performance. The sample used in this research was 200 SMIs registered in the Department of Industry and Trade of Bandung. The method used was quantitative methods, survey, and descriptive research. The data was collected through questionnaires and interviews with the Head of the Department of Industry and Trade and the business managers. The testsconducted werevalidity and reliability test,while the scale used was the Likert Scale. The strategy implementation was analysed using Importance Performance Analysis (IPA). The results of the study show that the performance of food and non-food SMIs could be improved and developed.therefore, SMIs have to do several things, namely developing their marketing goals, developing their marketing areas, setting prices according to the packaging, developing their marketing channels, and maintaining product characteristics. The method of marketing used by the sample is good. The strategies used by food and non-food SMIs lie on the top priority quadrants by making continuous improvements so that the level of marketing performance increases. The sample developed its marketing objectives and marketing areas by taking into account the desires and needs of consumers. The business managers of food and nonfood SMIs should: improve their marketing method through concepts, strategies, and market intelligence as well as maximize the use of the internet. Meanwhile, future researchers are suggested to expand research locations and add innovation and creativity variables to obtain better and comprehensive results.